A REVIEW OF RINDIK MUSIC ADAPTATION IN THE WELLNESS TOURISM DEVELOPMENT - Sari, Evi Thelia (Proceeding Bali-Bhuwana Waskita: Global Art Creativity Conference, 2024)
This article aims to analyze how the Rindik music adapts to the development of wellness tourism while maintaining the Balinese culture. The review focuses on the process of Rindik music adaptation in wellness tourism context and how it is adapted without sacrificing the culture essence. The qualitative research is used in this article by literature study processed by NVivo. The observation is used to support the thematic analysis. The result of this research found 4 adaptation components of Rindik music to show how the Rindik music adapts in the context of wellness tourism development, namely existence, direction, elements and triggers of adaptation. The existence indicates the changes and development and the direction refers to freedom to meet the market demand. The third component, elements of adaptation consist of method, sound, instruments, therapy, notes, traditional and value. The last component, triggers, can be listed as people, tourism, and culture.